Perspective—6G and IoT for Intelligent Healthcare: Challenges and Future Research Directions - Abdul Ahad; Mohammad Tahir (ECS Sensors Plus, 2023)
Due to the rise of connected devices, a decentralised, patient-centred paradigm is being adopted in healthcare as an alternative to the traditional hospital and specialist-focused approach. As the healthcare sector expands, more applications will be connected to the network, producing data of various shapes and sizes that will allow for customised and remote healthcare services. Future intelligent healthcare will include a combination of 6G and the Internet of Things (IoT) that will address current limitations related to cellular coverage, network performance and security issues. This paper discusses and sheds light on prospects, associated challenges and future directions.